Advanced directives in capacity-affecting diseases: the medico-legal perspective - Bolcato, Vittorio; Fassina, Giovanni; Conti, Adelaide; De Luca, Antonio; Basile, Giuseppe; Tronconi, Livio (Acta Biomedica Atenei Parmensis, 2024)
Advanced directives (ADs) and the activation of additional instruments of legal representation in health, in various neuropsychiatric and geriatric settings, nowadays are the tools to support the entitled subject decision-making in healthcare. However, even after Italian Law n. 219/2017 on informed consent and advanced treatment directives, many controversial aspects remain with respect to the entitled subject’s autonomy and thus to the full application of the law. The temporal dissonance between care planning and health intervention was one of the main cons, while the entitled subject reference compared to caregivers and practitioners was the main pro. In terms of practical application, the lack of knowledge and practice of ADs by citizens on the one hand, and the poor reference and valorisation to ADs by healthcare professionals on the other, were discussed. No less the frequent reference by the healthcare practitioners to the family members or surrogates in the health choices for the subjects with neuro-psychiatric diseases, or in geriatric setting, results critical, in particular when deviating from settled ADs. Furthermore, the figure of the trustee, as a simple reference for the ADs, is compared to the function of the health guardian, endowed with specific powers of representation; the latter often belatedly and improperly involved in health choices. Some insights from daily consulting activities are proposed for clinical practice, particularly with respect to contingent choices, while highlighting the need to use the appropriate tools provided by law. The regularly updated ADs together with the health guardian function, despite some limitations, fully respond to the need to guarantee clinically, legally, and ethically the entitled person’s autonomy and the balancing of rights.